2021
DOI: 10.3389/fnut.2021.772903
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the in vitro Activities of α-Amylase and Pancreatic Lipase by Aqueous Extracts of Amaranthus viridis, Solanum macrocarpon and Telfairia occidentalis Leaves

Abstract: Inhibition of digestive enzymes such as α-amylase and pancreatic lipase (PL) is a promising therapeutic strategy for the treatment and management of chronic health conditions such as diabetes and obesity. Therefore, the aim of this work was to determine the enzyme inhibitory activity of polyphenol-rich aqueous extracts of Amaranthus viridis (AV), Solanum macrocarpon (SM) and Telfairia occidentalis (TO) leaves, which were harvested from plants produced using multiple urea fertilizer doses (0–80 kg N/ha). Fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 68 publications
(95 reference statements)
2
11
1
Order By: Relevance
“…Figure 3a revealed a significantly higher (p<0.05) product produced from the α-amylase enzyme reaction incubated at 50 °C temperature as compared with the room and 37 °C temperatures. This is in contrast with the most reported papers including Keharom et al (2016), Simair et al (2017), and Oluwagunwa et al (2021) which showed the ability of alpha-amylase enzyme to react at the range of 37-39 °C temperatures. However, Xiao et al (2006) demonstrated that the alpha-amylase enzyme was mostly active after 30 min of incubation at 50 °C.…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…Figure 3a revealed a significantly higher (p<0.05) product produced from the α-amylase enzyme reaction incubated at 50 °C temperature as compared with the room and 37 °C temperatures. This is in contrast with the most reported papers including Keharom et al (2016), Simair et al (2017), and Oluwagunwa et al (2021) which showed the ability of alpha-amylase enzyme to react at the range of 37-39 °C temperatures. However, Xiao et al (2006) demonstrated that the alpha-amylase enzyme was mostly active after 30 min of incubation at 50 °C.…”
Section: Resultscontrasting
confidence: 78%
“…The validated proposed method was employed to determine the optimum condition for α-amylase enzyme reaction. The conditions tested were the concentrations of the enzyme (2, 4, 6, 8, 10 U/mL) and starch (1, 2, 3, 4, 5% w/v) incubated at three different temperatures, including room temperature (Oyedemi et al, 2017), 37 °C (Oluwagunwa et al, 2021) and 50 °C (Xiao et al, 2006). An amount of 20 µL of 0.02 M sodium phosphate buffer containing 0.006 M of sodium chloride (pH 6.9) was mixed with 20 µL of soluble starch and 20 µL of α-amylase enzyme solution.…”
Section: Utilization Of the Developed Methods For The Optimization Of...mentioning
confidence: 99%
“…The inhibition of PL mitigates excessive fat deposition in the adipose tissue ( 3 ). The results of PL inhibitory activity of the P. vicina extract with or without shaking are shown in Figure 3A .…”
Section: Resultsmentioning
confidence: 99%
“…Obesity, which is characterized by excessive accumulation of body fat and aberrant lipid metabolism, is associated with an increased risk of disability. Thus, the enzymes, including pancreatic lipase (PL), involved in lipid metabolism are potential therapeutic targets for obesity ( 3 ). Oxidative stress, a major source of free radicals, is the etiological factor for various chronic diseases, such as type 2 diabetes mellitus, cardiovascular disease, chronic inflammation, cancer and metabolic dysfunction ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The far and near UV spectra of the enzyme -peptide complexes were determined as described by Oluwagunwa et al (21). The final assay solution (200 µl) was a mixture of enzyme (100 and 350 µg/ml for far and near-UV, respectively), peptide (12.5 -50 µg/ml), which were all prepared in 0.1 M phosphate buffer (pH 7.4).…”
Section: Circular Dichroic Spectra Of the Acetylcholinesterase-peptid...mentioning
confidence: 99%